Aspekty sprawności sportowej w rywalizacji tanecznej par tańca sportowego stylu standardowego na podstawie oceny wyników próby wytrzymałości 20 m – bieg wahadłowy = Aspects of fitness sports pairs dance in dance competition sports style standard performance assessment tests strength – 20 m gear swing - Pilewska, Wiesława; Matczak, Paweł (Journal of Education, Health and Sport, 2015)
Pilewska Wiesława, Matczak Paweł. Aspekty sprawności sportowej w rywalizacji tanecznej par tańca sportowego stylu standardowego na podstawie oceny wyników próby wytrzymałości 20 m – bieg wahadłowy = Aspects of fitness sports pairs dance in dance competition sports style standard performance assessment tests strength – 20 m gear swing. Journal of Education, Health and Sport. 2015;5(11):595-605. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35706 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A595-605 http://pbn.nauka.gov.pl/works/684904 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Pilewska Wiesława, Matczak Paweł. Aspekty sprawności sportowej w rywalizacji tanecznej par tańca sportowego stylu standardowego na podstawie oceny wyników próby wytrzymałości 20 m – bieg wahadłowy. Quality in Sport. 2015;1(1):45-54. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Wiesława Pilewska, Paweł Matczak Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Aspekty sprawności sportowej w rywalizacji tanecznej par tańca sportowego stylu standardowego na podstawie oceny wyników próby wytrzymałości 20 m – bieg wahadłowy Aspects of fitness sports pairs dance in dance competition sports style standard performance assessment tests strength – 20 m gear swing Streszczenie Cel pracy W niniejszej pracy podjęto próbę charakterystyki poziomu zdolności wytrzymałościowych par C-S klasowych tańca sportowego stylu standardowego w odniesieniu do aspektów sportowej działalności tanecznej. Materiał Grupę badawczą stanowiły sportowe pary taneczne, trenujące w Toruńskim Klubie Tanecznym Dance & Dance. Grupa liczyła 22 osoby tworząc 11 par. Wiek badanych mieścił się w przedziale 16-22 lata. Grupa na turniejach prezentowała grupę wiekową powyżej 15 lat. W badanej grupie dwie pary prezentowały klasę „C”, sześć klasę „B”, dwie pary klasę „A”, jedna para klasę „S”. Metody badawcze Do pomiaru wytrzymałości wykorzystano 20-metrowy bieg wahadłowy. Test polegał na pokonywaniu 20 metrowych odcinków w określonym czasie. Sygnały określające tempo znajdowały się na nagraniu pozyskane ze strony Narodowego Centrum Badania Kondycji Fizycznej (ncbkf.pl). Niemożność utrzymania tempa lub spóźnienie się na sygnał oznaczający rozpoczęcie kolejnego cyklu, był znakiem do ukończenia testu. Wyniki i wnioski W grupie tancerzy C-S klasowych, stylu standardowego odnotowano istotną statystycznie p≥0,01 współzależność pomiędzy uzyskiwanymi wynikami próby 20 metrowego biegu wahadłowego a ich poziomem sportowym. We wszystkich grupach (tancerzy i tancerek) odnotowano wprost proporcjonalny charakter współzależności pomiędzy wynikiem sportowym a poziomem zdolności wytrzymałościowych (określonych wynikami 20 metrowego biegu wahadłowego). Na przykładzie najlepszych par wnioskować można że profil pary powinien ukazywać dominację partnera w poziomie wytrzymałością a ich partnerki powinny prezentować 60-70% poziomu partnera. Zarówno mniejsza jak i większa różnica wykazują tendencję do słabszych wyników sportowych i charakteryzowała pary o niższym poziomie sportowym. Słowa kluczowe: taniec towarzyski, styl standardowy, 20-metrowy bieg wahadłowy, poziom sportowy. Abstract Aim of the study In this paper, an attempt to level the characteristics of endurance capacity C-S couples sporty style dance class standard in relation to aspects of dance sport activities. Materials The research group sports were couples dancing, Training in Torun Club & Dance the Dance Dance. The group consisted of 22 people forming 11 pairs. The age of respondents ranged from 16-22 years. The group presented the age-group tournaments over 15 years. In the group of two pairs presented a class "C" six class "B", two pairs of class "A", one pair of class "S". Research Methods Used to measure the strength of a 20-meters gear swing. The test was to overcome the 20 meters sections at a given time. Signals determining the pace were on record obtained from the National Center for the Study of Physical Constitution (ncbkf.pl).Inability to keep pace or late in the signal indicating the start of the next cycle, was a sign to complete the test. Results and conclusions In the group of dancers C-S class, style standard p≥0,01 reported a statistically significant correlation between the results of those obtained sample of 20 meters gear swing and their level of sport. In all groups (dancers) were recorded directly proportional nature of the correlation between the outcome and the level of sports endurance capacity (specific results of 20-meters gear swing). For example, the best pairs can be inferred that the profile should show the dominance of a partner in the level of strength and their partners should represent 60-70% of the partner. Both smaller and larger difference tend to be weaker performance was characterized by a pair of sports and a lower level of sports. Key words: ballroom dancing, style standard, 20-meters gear swing, sports level.